The role of charge-exchange processes in probing hydrogen plasma with a heavy ion beam - Inga Yu Tolstikhina; V. P. Shevelko (Matter and Radiation at Extremes, 2023)
Charge-changing processes of low-charged ions, used in hydrogen plasma probing by the heavy ion beam probe method, are considered. Along with the ionization of beam ions by plasma electrons and protons, the charge-exchange processes of ions on H atoms and protons are also studied. It is shown that charge exchange of beam ions on plasma protons and H atoms, which is rarely taken into account, plays an important role in beam–plasma interaction. New data on the cross sections and rates of ionization and charge-exchange processes are presented for Tl+ and Tl2+ ions, which are frequently used for plasma diagnostics. Calculations are performed for hydrogen plasma temperatures Te = 1 eV–10 keV and densities Ne = 1012–1014 cm−3 at relatively low and high ion-beam velocities vb = 0.2 and 1.0 a.u., respectively. Special attention is paid to the determination of the electron temperatures at which the charge-exchange processes on H atoms and protons are important. Multiple ionization of beam ions by plasma electrons and protons is briefly discussed.